Enzyme-bound Intermediates in the Biosynthesis of Mevalonic and Palmitic Acids - Jonathan D. Brodie; Gertrude Wasson; John W. Porter (1964)
t’ion. Direct proof that mevalonic and fatty acid syntheses are accomplished by an avian enzyme system through enzyme-bound intermediates was provided in a preliminary communication from our laboratory (3). Direct proof of the formation of enzyme-bound intermediates in fatty acid biosynthesis by an enzyme preparation of Escherichia coli was provided earlier in reports of the isolation of acetoacetyl-enzyme (4) and its conversion to butyryl-enzyme (5) and long chain fatty acids (4), and a report of the conversion of butyryl-enzyme to caproylenzyme (5). Earlier work by Lynen (6) also established that acetoacetyl-enzyme is formed by a particulate yeast enzyme system partially purified for the synthesis of fatty acids. The recent preliminary communication from our laboratory (3) provided the first direct evidence that the formation of malonyl-enzyme is the initial step in the synthesis of mevalonic and fatt,y acids by a pigeon liver enzyme system. Dat.a were presented to show that radioactivity of malonyl-enzyme was incorporated into @-hydroxy-P-methylglutaryl coenzyme A as well as into long chain fatty acids. In the present report this information is amplified and extended to include the synthesis of acetoacetyl-enzyme, butyryl-enzyme, and &ketohesanoylenzyme from malonyl-enzyme. Data are also presented to show the formation of acetyl-enzyme and butyryl-enzyme, and the synthesis of fatty acids from each of these compounds. The possibility that a long chain polyketo compound might be formed as an intermediate has also been investigated. No evidence was obtained to support, this proposal.